The effect of Audio Lingual Method and Using Animation video on the Students Achievement in Speaking Skill - Deka, Ulfa; Putri, Rini Fadhillah (Universitas Negeri Medan, 2023)
Many students do not speak English well, are not confident in speaking, some are afraid of making mistakes in pronunciation. The purpose of this research is to find the effect of the Audio- Lingual Method on speaking achievement, This research was conducted using quantitative methods. The research sample consisted of 20 students in class VIII-1 as the experimental class with Treatment Using Audio Lingual Method and 20 students in class VIII-2 as the control class with Conventional. From the data that has been analyzed, researchers obtained the average results of the experimental class the highest average score was 95 and the lowest average score was 85. In addition, in the control class the total score of 20 students was 1.815 and the average score is 90.75 points. And the control class the highest average score was 85 and the lowest average score was 75. Moreover, in control class the total score that 20 students was 1.590 and the average score was 79,5 point. Students' speaking skills can be improved by using the Audio Lingual Method and Using Animation Video.